THE ROLE OF THERAPEUTIC EXERCISES IN ENHANCING FUNCTIONAL PERFORMANCE AND QUALITY OF LIFE IN WOMEN WITH KNEE OSTEOARTHRITIS - Nath, Somnath; Jain, Annu; Agarwal, Archana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Knee osteoarthritis (OA) is a prevalent degenerative joint disease that significantly impacts functional performance and quality of life, particularly in women. This study investigates the efficacy of therapeutic exercises in improving functional outcomes and quality of life for women with knee OA. A systematic review and meta-analysis of randomized controlled trials were conducted to evaluate the effects of various exercise interventions. The results demonstrate that structured exercise programs, including aerobic, strengthening, and flexibility exercises, lead to significant improvements in pain reduction, physical function, and quality of life measures. The findings highlight the importance of tailored exercise interventions as a non-pharmacological approach to managing knee OA in women and underscore the need for long-term adherence to exercise regimens for sustained benefits.